Discotic Liquid Crystal Epoxy Resins Integrating Intrinsic High Thermal Conductivity and Intrinsic Flame Retardancy. Issue 1 (17th October 2021) - Zhong, Xiao; Yang, Xutong; Ruan, Kunpeng; Zhang, Junliang; Zhang, Haitian; Gu, Junwei
Abstract: The integration of intrinsic thermal conductivity and intrinsic flame retardancy of epoxy resins shows wider application prospects in electricals and electronics. Discotic liquid crystal epoxy (D‐LCE) is synthesized from pyrocatechol, 2‐allyloxyethanol, and 3‐chloroperoxybenzoic acid. P/Si synergistic flame‐retardant co‐curing agent (DOPO‐POSS, DP) is synthesized from p‐hydroxybenzaldehyde, 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene 10‐oxide (DOPO), and amino terminated polysilsesquioxane (POSS). Finally, D‐LCE is cured within liquid crystal range with 4, 4′‐diaminodiphenyl methane (DDM) and DP, to obtain intrinsic highly thermal conductive/flame‐retardant epoxy resins (D‐LCERDP ). D‐LCERDP‐10.0 (10.0 wt% DP) synchronously possesses excellent intrinsic thermal conductivity and intrinsic flame retardancy, with thermal conductivity coefficient in vertical and parallel direction ( λ ⊥ and λ ∥ ) of 0.34 and 1.30 W m −1 K −1, much higher than that of general bisphenol A epoxy resin (E‐51, λ ⊥ of 0.19 W m −1 K −1, λ ∥ of 0.65 W m −1 K −1 ). The limiting oxygen index (LOI) value of D‐LCERDP‐10.0 reaches 31.1, also better than those of E‐51 (19.8) and D‐LCER (21.3). Abstract : A new method is offered to achieve the integration of intrinsic thermal conductivity and intrinsic flame retardancy. Novel liquid crystal epoxy and co‐curing agent are synthesized by introducing discotic liquid crystal structure and P/Si synergistic flame‐retardant groups, respectively. The prepared epoxy resins synchronously possess excellent intrinsic high thermal conductivity and intrinsic flame retardancy.